Restorative Justice against the Crimes of Murder based on Noodweer and Noodweer Exces - Aulia Sherliantie, Devanie; Hadi Pura, Margo; Fadlian, Aryo (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
Cases of Noodweer and Noodweer Exces often occur in society, and it is often found that they are still can be a subject to criminal penalties. Article 49 of the Crime Code states that the Noodweer and Noodweer Exces are one of the reasons for the abolition of criminal penalties. Then, why are there still perpetrators of the crime of murder who carry out a Noodweer and Noodweer Exces can still be subject to criminal sanctions? Can this problem be solved through restorative justice? What is the judge's consideration in cases where the suspect commits a crime of murder and carries out an Noodweer and Noodweer Exces?. The presence of restorative justice as a new solution in resolving cases is one of the main keys in the process of resolving a criminal case that is fast, simple, and inexpensive. Based on article 49 of the Crime Code regarding the elimination of crimes against the perpetrators of the Noodweer and Noodweer Exces murders, Restorative Justice as a case settlement solution is expected to be applied in the Noodweer and Noodweer Exces cases in order to create an agreement on the settlement of a criminal case and obtain a fair and equitable outcome between the victim and the perpetrator.